2021
DOI: 10.1186/s13690-021-00762-6
|View full text |Cite
|
Sign up to set email alerts
|

Promoting outdoor recreation among older adults in Sweden – a theoretical and empirical foundation for the development of an intervention

Abstract: Background Disengagement from outdoor recreation may diminish the positive benefits on health and well-being in old age. The purpose of this study is to present a contextual, theoretical, and empirical rationale for an intervention, aiming to promote continued engagement in outdoor recreation for older adults in a Swedish context. Methods The paper includes a contextualization of outdoor recreation in Sweden, a presentation of evidence on health be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…More than half of them had disengaged from walking which they had practiced in the previous year. They cited declining health as the most common reason, but some found it too demanding or mentioned possible social context change [5]. But in another study those continuing active, social outdoor activity reported happiness, and the positive feelings made outdoor activity appealing and increased their likelihood of persisting [6].…”
Section: Maintaining Outdoor Activity For Older Peoplementioning
confidence: 99%
See 3 more Smart Citations
“…More than half of them had disengaged from walking which they had practiced in the previous year. They cited declining health as the most common reason, but some found it too demanding or mentioned possible social context change [5]. But in another study those continuing active, social outdoor activity reported happiness, and the positive feelings made outdoor activity appealing and increased their likelihood of persisting [6].…”
Section: Maintaining Outdoor Activity For Older Peoplementioning
confidence: 99%
“…Research (and indeed common sense) suggests that physical function should affect the convenience of outdoor activities [5]. Some factors affecting physical function are well understood, but social economics could also be relating to health and physical function.…”
Section: Social Factors and Pain Indirectly Affect Coa Through Relati...mentioning
confidence: 99%
See 2 more Smart Citations
“…According to Zingmark et al, (2021), local parks provide space for physical activity; these natural places should be regarded as part of a plan for health promotion and illness prevention among older individuals. The definition of "outdoor recreation" thus encompasses nature experiences that have consequences for health and well-being, but it is wide in terms of both the sorts of activities undertaken and the types of natural surroundings encountered (Zingmark et al, 2021).…”
Section: Leisure Activities and Well-beingmentioning
confidence: 99%